Clinical Relevance of Gain- and Loss-of-Function Germline Mutations in STAT1: A Systematic Review - Zhang, Wenjing; Chen, Xuemei; Gao, Guodong; Xing, Shubin; Zhou, Lina; Tang, Xuemei; Zhao, Xiaodong; An, Yunfei (Frontiers in Immunology, 2021)
BACKGROUND: Germline mutations in signal transducer and activator of transcription 1 (STAT1), which lead to primary immunodeficiency, are classified as defects in intrinsic and innate immunity. To date, no comprehensive overview comparing GOF with LOF in early-onset immunodeficiency has been compiled. OBJECTIVE: To collect and systematically review all studies reporting STAT1 GOF and LOF cases, and to describe the clinical, diagnostic, molecular, and therapeutic characteristics of all the conditions. METHODS: A systematic review of the PubMed, EMBASE, Web of Science, Scopus, and Cochrane to identify articles published before May 23, 2020. Data pertaining to patients with a genetic diagnosis of STAT1 GOF or LOF germline mutations, along with detailed clinical data, were reviewed. RESULTS: The search identified 108 publications describing 442 unique patients with STAT1 GOF mutations. The most common manifestations in STAT1 GOF mutations were chronic mucocutaneous candidiasis (CMC; 410/442), lower respiratory tract infections (210/442), and autoimmune thyroid disease (102/442). Th17 cytopenia was identified in 87.8% of those with GOF mutations. Twenty-five patients with GOF mutations received hematopoietic stem cell transplantation (HSCT), and ten died several months later. Twelve of 20 patients who received JAK inhibitor therapy showed improved symptoms. Twenty-one publications described 39 unique patients with STAT1 LOF mutations. The most common manifestations were Mendelian susceptibility to mycobacterial diseases (MSMD) (29/39), followed by osteomyelitis (16/39) and lymphadenopathy (9/39). Missense, indel, and frameshift mutations were identified as LOF mutations. There were no obvious defects in lymphocyte subsets or immunoglobulin levels. Eighteen patients required antimycobacterial treatment. Three patients received HSCT, and one of the three died from fulminant EBV infection. CONCLUSIONS: STAT1 GOF syndrome is a clinical entity to consider when confronted with a patient with early-onset CMC, bacterial respiratory tract infections, or autoimmune thyroid disease as well as Th17 cytopenia and humoral immunodeficiency. HSCT is still not a reasonable therapeutic choice. Immunoglobulin replacement therapy and JAK inhibitors are an attractive alternative. STAT1 LOF deficiency is a more complicated underlying cause of early-onset MSMD, osteomyelitis, respiratory tract infections, and Herpesviridae infection. Anti-mycobacterial treatment is the main therapeutic choice. More trials are needed to assess the utility of HSCT.